Two cases of complex traumatic aortic dissection combined with multiple organ injuries - Qingpeng Song; Lili Bao; Xuejun Wu; Bingqi Liu; Maohua Wang (Chinese Journal of Traumatology)
Traumatic aortic injury (TAI) is an acute, critical, and severe disease, and then combined with multiple organ damage, it is even more dangerous. TAI progresses very rapidly, with a pre-hospital mortality rate of 57%–80%, and even when arriving at the hospital, more than one-third of the patients die within 4 h, and it is the 2nd leading cause of death in individuals aged 4−34 years. In addition, the incidence of TAI combined with injury was 81.4%. Therefore, early diagnosis, expeditious surgery, and timely and effective multidisciplinary cooperation are essential for successful rescue. The authors report 2 patients with acute traumatic aortic dissection combined with multiple organ injuries and treated with emergency endovascular surgery to discuss their clinical characteristics and treatment experience, and to provide experience in the diagnosis and treatment of such patients.